Miniinvasive vascular interventions as an alternative surgical method for treatment of the patients, suffering hepatic cirrhosis and portal hypertension - О. F. Dzygal; І. М. Deykalo (Клінічна хірургія, 2018)
Objective. Determination of efficacy of miniinvasive surgical treatment of portal hypertension (PG) in patients, suffering hepatic cirrhosis (HC) in immediate and late postoperative periods.